The first observation of seismicity beneath the northwestern Ethiopian plateau and its seismotectonic implications - Alemayehu, Sisay; Ayele, Atalay; Keir, Derek (Frontiers in Earth Science, 2025)
The seismotectonics of the Northwestern (NW) Ethiopian plateau and the adjacent rift flanks were studied using local earthquake data recorded by broadband seismic networks. This include stations from the Ethiopian plateau network (2014–2016) as well as seven permanent Ethiopian seismic stations. A total of 800 earthquakes, with magnitudes ranging from ML∼1.1 to 4.6 were located. Seismicity clustered beneath the NW plateau, Fentale volcano, and the Guraghe border fault of the Main Ethiopian Rift (MER). The detected seismic activity beneath the NW plateau is the first observation ever made in the area, supporting recent tomographic investigation results indicating the presence of partial melt and magmatic activity. This result further show that the NW plateau exhibits greater tectonic activity relative to the southeasten plateau of the MER. Moment tensor inversion is conducted using ISOLA software for few earthquakes in the magnitude range Mw 3.7 to 4.6. We obtained a dominantly normal faulting earthquake of magnitude 3.7 at 14 km depth beneath the NW plateau implying extensional tectonics. We interpret that active thermal degradation and crustal heterogeneity contributes to the seismicity beneath the NW plateau, where cumulative observations may indicate distributed extension.